(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
The study investigates students’ attitudes toward the integration of a digital storytelling project into a foreign language classroom with a particular interest in improving writing narrative paragraphs and in promoting 21st century communication skills. The research was conducted with 36 students at the University of Ghardaia, Algeria, who volunteered to participate in a four week DST project. The study used both quantitative and qualitative research methods. An online survey was conducted for the quantitative method, and a semi structured interview for the qualitative method to get in depth insights about students’ perceptions of the project. The results of the survey were received from 32 students out of 36 while 18 students with low proficiency and confidence in English were selected to take part in the interview. The findings reveal that digital storytelling project in a technological learning environment has great potential to foster students’ communication skills and improve their writing skill when collaborating with peers as opposed to traditional classes.